Impact of digital villages construction on agricultural green production efficiency: evidence from China - Lei, Xian Kai; Chen, Yong Xin (Frontiers in Sustainable Food Systems, 2025)
Digital villages construction and agricultural green development are key factors in promoting the high-quality development of agriculture in China. This paper takes the period from 2012 to 2023 as the sample observation period and employs a fixed-effects model to empirically analyze the impact of digital villages construction on agricultural green productivity in 30 provinces of China, as well as the underlying mechanisms. The results show that: (1) From 2012 to 2023, the level of agricultural green production efficiency in China has been steadily increasing, with technological progress being the core driving force for this growth; (2) The level of digital villages construction significantly enhances agricultural green production efficiency. After a series of robustness and endogeneity tests, the results remain valid; (3) Mechanism tests reveal that the level of rural human capital plays a mediating role in this process; (4) The spatial spillover effect test indicates that digital villages construction has a positive spatial spillover effect on agricultural green production efficiency.